1991
DOI: 10.3109/02652049109071487
|View full text |Cite
|
Sign up to set email alerts
|

Poly(hydroxybutyrate-hydroxyvalerate) microspheres containing progesterone: Preparation, morphology and release properties

Abstract: The biodegradable polyesters, poly(hydroxybutyrate) (PHB) and poly(hydroxybutyrate-hydroxyvalerate) (PHBV) were investigated for use as sustained delivery carriers of a model drug, progesterone. Spherical microspheres containing the drug were prepared by an emulsion solvent-evaporation method with gelatin as an emulsifier. Methylene chloride as the polymer solvent yielded smoother microspheres than chloroform. The surface texture was also dependent upon the temperature of the preparation and polymer used. Surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(28 citation statements)
references
References 19 publications
0
27
1
Order By: Relevance
“…50/50, 85/15, 100/0) and changes in initial drug loading (data not shown). Gangrade et al found that changing the emulsifying agents (PVA to gelatin) significantly altered the microspheres properties (44). However, in our study, changing the emulsifying agent from PVA to gelatin in the external aqueous phase during the fabrication process did not affect the phase separation of FA from PLGA.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…50/50, 85/15, 100/0) and changes in initial drug loading (data not shown). Gangrade et al found that changing the emulsifying agents (PVA to gelatin) significantly altered the microspheres properties (44). However, in our study, changing the emulsifying agent from PVA to gelatin in the external aqueous phase during the fabrication process did not affect the phase separation of FA from PLGA.…”
Section: Discussioncontrasting
confidence: 56%
“…Residual DCM was not measured in the final microsphere products of this study. However, using similar processing conditions, Gangrade et al have shown there was no detectable amount of residual DCM in the microspheres (43,44). FA-loaded PHBV microspheres were fabricated using the same procedures described above.…”
Section: Fabrication Of Fa-loaded Plga and Phbv Microspheresmentioning
confidence: 98%
See 1 more Smart Citation
“…PHBV belongs to the group of polyhydroxyalkanoates (PHAs), polyesters naturally synthesized by microorganisms and deposited intracellularly as insoluble spherical inclusions [Grage et al, 2009]. Its characteristics of biocompatibility and biodegradability make PHBV attractive for numerous applications in medicine, including drug delivery systems [Reis et al, 2006;Poletto et al, 2008;Grage et al, 2009;Franceschi et al, 2008;Gangrade and Price, 1991;Sendil et al, 1999]. PHBV is a more attractive polyester than PHB because it has a lower degree of crystallinitty and this property can be changed as a function of the hydroxyvalerate content [Modi et al, 2011].…”
Section: Introductionmentioning
confidence: 99%
“…The use of biodegradable hydrophobic polymers, [poly(lactic acid), poly(glycolic acid), poly(e-caprolactone), poly(hydroxy alkanoates)], [1][2][3][4][5] and later on amphiphilic polymers [poly(lactide-coglycolide), poly(lactide)-poly(ethylene glycol)] [6][7][8] appeared as a great promise. Obtaining of such systems requires, in most of the cases, aggressive conditions (organic solvents, high temperature, sonication etc), which may compromise the stability of the included molecules.…”
Section: Introductionmentioning
confidence: 99%